Asymmetric dimethylarginine in psychiatric disorders. (June 2021) - Braun, Daniel; Schlossmann, Jens; Haen, Ekkehard
Highlights: Serum concentrations of ADMA in patients with schizophrenia, schizoaffective disorder, bipolar disorder, and depression are elevated compared to healthy individuals. ADMA levels in patients with recurrent depressive disorder are elevated compared to patients with one depressive episode. ADMA concentrations do not differ between women and men. ABSTRACT: Serum concentrations of asymmetric dimethylarginine (ADMA) in patients with schizophrenia, schizoaffective disorder, bipolar disorder, and depression were determined and compared to serum concentrations in healthy individuals. In all psychiatric diseases investigated, the ADMA concentration was elevated compared to the control group. Patients with recurrent depressive disorder had higher ADMA levels than patients with only one depressive episode. No differences between women and men were found. The elevated ADMA levels suggest that ADMA is involved in the pathophysiology of psychiatric diseases.